2022
DOI: 10.1016/j.ajog.2021.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of infection-induced SARS-CoV-2 seropositivity throughout gestation

Abstract: The SARS-CoV-2 immunoglobulin G (IgG) antibodies increase approximately 2 to 3 weeks after viral infection. The time period for which these antibodies persist and how rapidly they decay have been the subject of several studies in nonpregnant patients, sometimes with differing results. 1e4 A study in pregnant women observed that the neutralizing antibody titers remained stable throughout gestation. 5 Our study evaluated the qualitative IgG antibody responses to SARS-CoV-2 infection longitudinally throughout pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
2
2
0
Order By: Relevance
“…We did not find any correlation between the presence of SARS-CoV-2 IgG antibodies or the ability to inhibit the virus and the development of preeclampsia. This result is consistent with previous studies [ 26 , 27 , 28 , 29 , 30 , 31 ]. However, Jemieson et al demonstrated a correlation between preeclampsia and severe COVID disease [ 32 ], while in a retrospective cohort study Ko et al observed a link between preeclampsia and any manifestation of SARS-CoV-2 infection [ 33 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We did not find any correlation between the presence of SARS-CoV-2 IgG antibodies or the ability to inhibit the virus and the development of preeclampsia. This result is consistent with previous studies [ 26 , 27 , 28 , 29 , 30 , 31 ]. However, Jemieson et al demonstrated a correlation between preeclampsia and severe COVID disease [ 32 ], while in a retrospective cohort study Ko et al observed a link between preeclampsia and any manifestation of SARS-CoV-2 infection [ 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…Staszewski et al analyzed SARS-CoV-2 IgG in 149 pregnant women in the first and second trimesters and at the time of delivery. They observed an antibody response throughout pregnancy, finding seropositivity between 12.1% and 16.1% [ 26 ], which is comparable to what we observed (seroprevalence: 19.7%, seroconversion: 12.1%) However, none of these studies analyzed the correlation between seroprevalence and clinical outcomes.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The reported prevalence of positive serological tests in pregnant women in our country varied from 15% in the first trimester [13], to 20% in the third trimester and delivery [13][14][15][16]. There is a smaller-scale study, carried out at three hospitals in New York, involving 149 women who were assessed for anti-SARS-CoV2 IgG antibodies during the first and second trimesters, as well as at the moment of delivery [17]. The outcomes from this study were similar to our own findings as the authors reported a seroprevalence rate of 12.1% during the first trimester and 16.1% during the second trimester.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%